Parametric computational analysis for punching shear in RC slabs. (15th June 2018) - Navarro, M.; Ivorra, S.; Varona, F.B.
Highlights: Numerical analysis of punching shear behaviour of RC slab-column connection. A Concrete Damage Plasticity model has been used. Qualitative and quantitative calibration with experimental results by other authors. Parametric study to analyse the influence of different variables. Steel and concrete strength, reinforcement ratio and geometrical ratios are analysed. Abstract: One of the key phenomena in flat slab structures is their punching shear behaviour. The real importance of punching shear consists of a sudden brittle fracture, which can trigger catastrophic consequences for humans. This paper presents a nonlinear numerical model based on finite elements in order to study the punching shear phenomenon of reinforced slabs. The numerical model developed has been configured with hexahedral 3D elements for concrete and linear elements (2D truss) for steel reinforcements. Constitutive equations for concrete and steel include the nonlinearity of these materials. The slab has been simulated in ABAQUS software and the model has been calibrated in comparison to experimental results developed in the University of Waterloo by Adetifa and Polak, and some additional analytical results developed by Polak, in order to validate the model. The calibration has also been contrasted with some experimental results from ACI database for punching tests. Afterwards, a parametric analysis has been performed to study the influence of different geometric and mechanical parameters which define a classic slab-column structure. This discussion also addresses the adequacy of some mechanical approaches, such as the CEB Model Code 2010.